Adventive grassy flora of the Botanical garden of Southern Federal University - Shmarayeva , A. N.; Shishlova , Zh. N. (Проблемы ботаники Южной Сибири и Монголии, 2019)
The specific structure and the short analysis of grassy fraction of adventive flora of the Botanical gardenof Southern Federal University (BS) is given in article. Adventive grassy flora contains 66 species of seed plants from 25families and 55 genuses that makes 9.1 % of the general structure of wild-growing flora of BS and 25.0 % of structureof sinanthropic flora of BS. The new adventive species to the Rostov region, – Parietaria chersonensis (Lang et Szov.)Dörfl., – was revealed.